Motivasi Pengusaha Muslim Memproduksi Produk Imitasi (Studi Pada Sentra Industri Kerajinan Kulit di Tanggulangin) - Firmansyah Aditama; Irham Zaki (Universitas Airlangga, 2015)
The purpose of this research is to know motivations which encourage moslementrepreneurs decide producing imitation product.This research used a qualitative approach with explanatory case study strategy which is able to answer the question arised. Data collecting process was done by interviewing moslem entrepereneurs in Tanggulangin. Analysis technique which used in this research is descriptive, because author tried to describe a symptoms, occurance, and events which happened nowadays. Author tried to capture events and occurance that happened and being a central of attention to be explained as it seen on the location.The result showed that there are many forms of motivation why moslem entrepreneurs decide to produce imitation products. Those motivations were classified and explained based on the Islamic motivation theory by Abdul Hamid Mursi. That motivation theory is physiological motivation, psychological or social motivation, and working and producing motivation.